2016
DOI: 10.7202/1035715ar
|View full text |Cite
|
Sign up to set email alerts
|

Adoucissement des eaux souterraines de la région orientale du Sahara septentrional algérien : cas de la région de Biskra

Abstract: Dans la ville de Biskra, l’alimentation en eau potable des habitants et l’irrigation des cultures reposent sur l’exploitation des eaux souterraines des aquifères du Sahara Septentrional. L’un des enjeux majeurs pour la durabilité de l’utilisation de cette ressource est la qualité des eaux de certains aquifères (Phréatique et Miopliocène). Ces dernières sont fortement minéralisées (entre 2 et 3 g∙L‑1 de sel dissous). Leur faciès chimique dominant est le sulfaté-chloruré avec un excès de chlorures, supérieur à l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Transmission through ingestion of contaminated water or items is the most common in the epidemiology of Salmonella. Contamination of the water environment with these germs is problematic and raises questions about their origin, survivability, and public health significance (Bouchemal, 2017). In our result, Salmonella were only present in station S5 located near the village of wadi Amlil (Table 5).…”
Section: Salmonellamentioning
confidence: 54%
“…Transmission through ingestion of contaminated water or items is the most common in the epidemiology of Salmonella. Contamination of the water environment with these germs is problematic and raises questions about their origin, survivability, and public health significance (Bouchemal, 2017). In our result, Salmonella were only present in station S5 located near the village of wadi Amlil (Table 5).…”
Section: Salmonellamentioning
confidence: 54%
“…When lime is used, precipitates of CaCO3 (pH 8 to 9) are formed. The zeta potential of CaCO3 is negative, which allows an attraction of mercury ions to the surface of the precipitate [37].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of an irrigation borehole, the samples were taken directly from the head of the borehole. In the case of a water tower, the samples were taken after the suspension of the bleaching process and emptying of the pipe [34]. In this study, a total of 72 water samples were collected during 2018-2021, which were identified with the number and coordinates of the water point, the date, and the depth and static level of the well.…”
Section: Sampling and Analysismentioning
confidence: 99%